A study on dermatological manifestations among chronic kidney disease patients undergoing hemodialysis in a tertiary care centre - R. V., Mookambika; Murugan, S. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic kidney disease (CKD) is a progressive loss of kidney function over a period of months or years through five stages. The prevalence of end-stage renal disease (ESRD) in India is increasing with an estimated annual incidence of about 100 per million populations. About 50-100% of patients with ESRD have at least one associated cutaneous change. These cutaneous disorders can precede or follow the initiation of hemodialysis treatment, and there are more chances to develop newer skin changes during the course of hemodialysis therapy, which may affect the quality of life. Objectives of the study was to find out the prevalence of various dermatological manifestations in patients undergoing hemodialysis in a tertiary care centre. Methods: A cross sectional study was carried out in the general medicine department of a tertiary care Centre. All cases of chronic kidney disease were diagnosed according to the criteria of KDQQI CKD guidelines, age group between 30-60 years are included. Pediatric patients with chronic kidney disease, patients who had renal transplantations, patients on peritoneal dialysis and renal injury patients are excluded. Results: Out of the 100 study participants majority are males (60%). Majority of the patients belongs to lower socioeconomic status family (59%). Atleast one dermatological manifestation was present in all patients. 23% of the patients presented with two dermatological manifestations and 22% of the participants had three or more dermatological manifestations. Xerosis was the most common dermatological manifestation present among the patients. Conclusions: This study reflects that quality of life in dialysis patients is mainly depend on timely recognition and prompt management of these dermatological conditions.